Ethical and Safety Aspects of the Use of ICT in Chemistry Education - Stárková, Dagmar; Rusek, Martin (Scientia in educatione, 2016)
Information and communication technology (ICT) has become an integral part of education. This brings not only a question of the eï¬ciency of these technologies, but also of the possible ethical and safety risk related to them. For teachers and students, it is important not only to be familiar with safety rules and the legal and moral principles underlying the use of ICT (especially on the Internet), but also to be capable of applying them correctly. This concerns above all the basic ethical codes and legislative framework. The paper is based on a survey which sought to categorize teachers according to their attitudes towards the use of ICT in chemistry education. A follow-up qualitative inquiry then seeks to survey the strategies the innovative teachers incorporate in terms of computer ethics and safety risk when using ICT in education. The respondents’ answers indicate that ICT is seen as an indisputable part of chemistry education. The results suggest that students use the Internet network to communicate, search for information, or to practice knowledge by means of online tests, applications or games. The teachers tended to emphasize citations of online sources as a potential ethical issue, with other ethical aspects (e.g. netiquette, diﬀerent applications of copyright law under licenses, etc.) taking the back seat. It also seems that teachers tend to underplay the signiﬁcance of safety aspects.